2016
DOI: 10.1175/jtech-d-15-0212.1
|View full text |Cite
|
Sign up to set email alerts
|

On-Orbit Absolute Calibration of the Global Precipitation Measurement Microwave Imager

Abstract: The Global Precipitation Measurement (GPM) Core Observatory was launched on 27 February 2014. One of the principal instruments on the spacecraft is the GPM Microwave Imager (GMI). This paper describes the absolute calibration of the GMI antenna temperature (TA) and the earth brightness temperature (TB). The deep-space observations taken on 20 May 2014, supplemented by nadir-viewing data, are used for the TA calibration. Data from two backlobe maneuvers are used to determine the primary reflector’s cold-space s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 19 publications
0
54
0
Order By: Relevance
“…(; 2015a). Subsequently, Wentz and Draper () concluded that GMI is the most accurate precipitation radiometer currently in space. To provide unified global precipitation estimates a reliable transfer standard of brightness temperatures (Tbs) between the GPM‐CO and the constellation partner precipitation sensors through the inter‐calibration of all the radiometer sensors has been established (Berg et al ., ).…”
Section: Observational Goals For Gpm Precipitation: Microphysical To mentioning
confidence: 99%
“…(; 2015a). Subsequently, Wentz and Draper () concluded that GMI is the most accurate precipitation radiometer currently in space. To provide unified global precipitation estimates a reliable transfer standard of brightness temperatures (Tbs) between the GPM‐CO and the constellation partner precipitation sensors through the inter‐calibration of all the radiometer sensors has been established (Berg et al ., ).…”
Section: Observational Goals For Gpm Precipitation: Microphysical To mentioning
confidence: 99%
“…The noise diode with GMI indicates no issues of radiometer nonlinearity [Draper et al, 2015b]. Deep-space maneuver has been performed to calibrate GMI against the cosmic background [Wentz and Draper, 2016]. As the cosmic background is homogeneous with known temperature, it has been found very useful to examine radiometer and refine APC algorithm with deep-space maneuver [Wentz et al, 2001;Weng et al, 2013a;H.…”
Section: Methodsmentioning
confidence: 99%
“…The APC algorithm has been examined and refined with comprehensive efforts through prelaunch test, onboard calibration system, deep-space maneuver, and simulation [Draper, 2014;Draper et al, 2015aDraper et al, , 2015bWentz and Draper, 2016]. For instance, results based on the deep-space maneuver estimate an accuracy of 0.1 K for TA and 0.25 K for TB [Wentz and Draper, 2016]. Problems such as the along-scan biases in warm scenes have been identified in early GMI data versions and subsequently corrected [Yang et al, 2015].…”
Section: Methodsmentioning
confidence: 99%
“…The GMI T A measurements are denoted by T A,gmi . The values for GMI η and χ are given by Wentz and Draper [2015].…”
Section: Satellite Versus Model Comparisonsmentioning
confidence: 99%
“…For example, a change in α D or α V of 0.00005 km −1 (0.0002 dB/km) produces a change of about 0.1 K in the ocean brightness temperature ( T B ) seen by a microwave radiometer onboard a satellite. The 0.1 K precision is typical of todays' advanced satellite microwave radiometers particularly after averaging over millions of space‐based observations [ Wentz and Draper , ]. The sensitivity of 0.00005 km −1 is much higher than is generally reported in the extensive literature on α D and α V [ Liebe , , , ; Clough et al , ; Liebe et al , ; Rosenkranz , ; Tretyakov et al , ; Payne et al , , ].…”
Section: Introductionmentioning
confidence: 99%